Perkin-Elmer gas chromatographs in use at EPA mobile laboratory - Perkin-Elmer Corporation (1972)
General view of chemist William A. Lonneman preparing an air sample for analysis by three Perkin-Elmer gas chromatographs in an Environmental Protection Agency (EPA) mobile laboratory. Per notations accompanying the photograph, the gas chromatographs were used to conduct compositional analyses of air samples from across the country in an effort to pinpoint polluters and study the parameters for the development of environmentally damaging pollutants, including hydrocarbons, oxides of nitrogen and sulfur, and other producers of photochemical "smog."
Keywords: United States. Environmental Protection Agency; Perkin-Elmer Corporation; Laboratories; Photochemical smog; Corporations; Gas chromatography; Air--Pollution; Gas chromatography--Instruments; Scientific apparatus and instruments; Chemists; Air--Pollution--Research